مقصد العقل في الصراع العربي الصهيوني - الصلاحات، سامي محمد حسن (جامعة الكويت - مجلس النشر العلمي, 2007)
مفهوم العقل الواعي يشكل أهمية بارزة في فهم مقتضيات القضية الفلسطينية وطبيعة الصراع العربي الصهيوني، إذ به يمكننا استدراك معالم هذا الصراع، والمؤامرات الدولية التي تحاك ضد المسلمين في فلسطين المحتلة، والمخططات التي يسعى الصهاينة لفرضها على المنطقة العربية والإسلامية. ولقد حاول الصهاينة قدر الإمكان العمل على تعطيل العقل العربي والسلم عن التفكير في كيفية القضاء عليهم، أو حتى مواجهتهم، من خلال مسكنات فكرية وسياسية وثقافية واجتماعية واقتصادية، وكلما حاول هذا العقل النزول إلى ساحات المعركة، اشغلوه بمعارك جانبية وهامشية؛ ليبتعد عن لب الصراع وأساسه. وفضلا على هذا كله، فرضوا عليه حلولا وطروحات، مثل: "السلام الزائف"، أو "التطبيع"، أو "فكرة الشرق الأوسط الكبير"، بحجج واهية، انطلت على بعض المفكرين العرب والمسلمين، وجعلوا المشكلة في المقاومة ومشروع الجهاد، وأن الاحتلال والمجازر التي يرتكبها العدو ضد المسلمين في فلسطين، هي أعمال للدفاع عن النفس، وللحفاظ على الأمن واستقرار المنطقة. في دراستنا هذه، سنحاول قدر الإمكان بيان أهمية دراسة العقل كمقصد شرعي أصولي، بحث-سابقا-في مباحث مقصاد الشريعة، وكيفية حفظه وجودا وعدما، مع بيان تطبيق هذه الدراسة على أهم صور الصراع العربي الصهيوني، وهو الاختلاف القائم بين المنهج الإسلامي الداعي للعودة إلى الجهاد والمقاومة إذ ذلك هو الطريق الشرعي المنطقي، في طرد المحتل اليهودي، في حين يرى غيرهم-وعلى الأخص العلمانيين واليساريون-بأن الصراع سياسي. هذه الدراسة ستبين أهم الفوارق بين هذين المنهجين، مع بيان بعض صور الصراع العقلي التي وقعت، وقد تقع بين المسلمين واليهود في هذه المعركة طويلة الأمد. The concept of conscious mind is very important in understanding the basics of Palestinian Case and the nature of Arab-Zionist conflict. Through it, we can realize features of this conflict and international conspiracies woven against Muslims in Occupied Palestine and Zionist plans and schemes aimed to be imposed on Arab-Islamic Area. Zionists have attempted, with all possible means, to derange and delude Arab-Muslim mind aiming at destroying it or even using intellectual, political, cultural, social and economic tranquilizers and mind anesthetics. Whenever the Arab mind tries to enter the battle field they create circumstances to engage it in marginal conflicts. Zionists will do every thing to alienate Arab mind and keep it distracted or away from the core of conflict. In addition to all those attempts they imposed solutions and propositions like "False Peace", Naturalization’ or ’The Idea of The Big Middle East’ giving faint reasons. Regretfully some Arab thinkers fell victims to these illusions thinking the problem was in resistance and jihad project. They adopted the Zionist point of view justifying Zionist massacres and occupation against Palestinians as only mere self-defense or defensive and security measures. In this study I try as possible as I can to stress the importance of Reason Intention as a Shariah fundamental. This was previously discussed in Research of Shariah Intentions. I am applying this study on the most important aspects of Arab-Zionist Conflict. This is the standing difference between Islamic methodology which calls for the return to jihad and resistance style as it has proved that it is logical and a Shariah approved way to expel Jewish occupants and regain lost rights.Whilst secularists and leftists claim that the conflict is merely a political conflict. This study shows the most important differences between the two methods and mentions forms of mental conflict which happened and may be repeated among Muslims and Jews in this long and continuous battle between good and evil purposes and forces in this world.
Keywords: المسلمون -- العقل -- القضية الفلسطينية -- الصراع العربي- الإسرائيلي -- اليهود -- الصهوينية -- فلسطين -- السلام -- المقاومة المسلحة -- الشريعة الإسلامية -- الأصوليون -- التطبيع -- العلمانية -- الهوية الإسلامية -- التعليم الجامعي -- اللغة العربية -- وسائل الإعلام